2020
DOI: 10.33545/gynae.2020.v4.i1c.459
|View full text |Cite
|
Sign up to set email alerts
|

Study of knowledge, attitude, and practice regarding cervical cancer and its screening among health service providers of Udaipur

Abstract: To Assess knowledge, attitude and practice towards cervical cancer and its screening among health service providers. Material and Methods: A cross-sectional study. Questionnaire was adapted from earlier studies related to cervical cancer and screening knowledge, attitude, and practices among female health care providers of Chennai cooperation 2013. Result: Out of 200 heath care providers 68.5% think that cancer cervix is a public health problem in India. 59% are aware about risk factors for acquiring cervical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Among 22 studies reviewed, 19 studies 15 25 , 27 – 30 , 32 35 reported knowledge of cervical cancer. The overall knowledge of cervical cancer among health professionals was 75.14%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among 22 studies reviewed, 19 studies 15 25 , 27 – 30 , 32 35 reported knowledge of cervical cancer. The overall knowledge of cervical cancer among health professionals was 75.14%.…”
Section: Resultsmentioning
confidence: 99%
“…The awareness level of risk factors was adequate. Among 22 studies, 14 studies 14 , 15 , 17 – 21 , 24 , 25 , 28 , 29 , 33 35 reported knowledge of risk factors of cervical cancer. The most common risk factor known was multiple sexual partners 44.07%, HPV infection 40.85%, and early age of marriage 38.52% ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations